Inflammation and DNA damage induction in surgical patients maintained with desflurane anesthesia - Arruda, Nayara M. [UNESP] (2019)
The use of anesthetics during surgical interventions may contribute to disorders in the perioperative period. Desflurane is the newest volatile halogenated anesthetic to be introduced in clinical practice. Considering that inflammation and genotoxicity are linked events, and that little is known regarding possible genetic and inflammatory effects of desflurane in surgical patients, this study evaluated DNA damage, systemic inflammatory cytokines and related gene expression in adult patients without comorbidities who underwent minor otorhinological surgeries under general anesthesia maintained with the inhalational anesthetic desflurane. This study involved a self-controlled design in which venous blood samples were collected from subjects before anesthesia administration and after the surgical procedure. The comet assay was applied to assess DNA lesions, while the cytokines IL-1β, IL-6, IL-8, IL-10, IL-17A and TNF-α were evaluated by flow cytometry. A genotoxic effect was observed (p = 0.027), and pro-inflammatory IL-6 and IL-8 levels were significantly increased after surgery (p = 0.001 and p = 0.02, respectively), whereas the levels of the other cytokines did not significantly change. Considering that serum IL-6 and IL-8 were increased, we further evaluated IL-6 and IL-8 gene expression by quantitative real-time polymerase chain reaction (qPCR). However, IL-6 and IL-8 gene expression was unaltered (p > 0.05). In conclusion, anesthetic maintenance with the modern agent desflurane during minor surgeries led to genotoxic and inflammatory effects without altering the expression of inflammation related-genes the day after surgery in patients without comorbidities.